Pengaruh Edukasi Menyusui Terhadap Tingkat Minat Ibu Antepartum Di Puskesmas Naman Teran Kabupaten Karo - Tarigan, Evita Sri Nova Br; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2025)
The achievement rate for exclusive breastfeeding in Indonesia in 2018 was 52% and in2020 it increased to 66.1% and has not yet reached the target set by the Ministry of Healthof 80%. One reason is the lack of interest in breastfeeding mothers. The lack of interest inbreastfeeding mothers requires the role of health workers, especially nurses, to provideeducation or health education. Education or health education about breastfeeding is veryimportant to increase the interest of breastfeeding mothers. The purpose of this study is toanalyze the effect of breastfeeding education on the level of interest of antepartum mothers.This research method is quantitative research with the type of pre-experimental researchusing a one group pre and post test design approach. The research was conducted at theNaman Teran Community Health Center, Karo District. The total population is 32 peopleand using total sampling technique. The data used are primary data and secondary data.Data analysis was performed univariately and bivariately using the Paired Sample T-test.The result showed that characteristics of antepartum mothers at the Naman Teran HealthCenter, Karo Regency, aged 20-35 years (78.1%), have secondary education (SMA)(40.6%), respondents work (56.3%), and have 2 children (43.8%). Before being givenbreastfeeding education, the majority of antepartum mothers had low interest (65.6%), thepretest average score was 8.13. After being given breastfeeding education, the majority ofantepartum mothers had a high interest (75.0%), the pretest average score was 12.53.There is an effect of providing breastfeeding education on the level of interest of antepartummothers at the Naman Teran Health Center, Karo Regency, with p-value = 0.000 <0.05 andtcount = -13.130 > ttable (1.694), there is an increase in interest score of 4.40 points. It can beconcluded that Breastfeeding education affects the level of interest of antepartum mothersto breastfeed. It is recommended that health workers always provide breastfeedingeducation to antepartum mothers so that mothers can increase their interest inbreastfeeding after giving birth.